DO CREATIVE AND INNOVATIVE LEADERSHIP AFFECT PRODUCT QUALITY? EVIDENCE FROM CULINARY MSMEs - Marianti, Maria Merry; Pratikna, Rizka Nugraha; Fernando, Fernando; Muntu, Cindy Keziea (Jurnal Aplikasi Manajemen, 2023)
The creative economy actors in Bandung City are dominated by culinary MSMEs. To survive in a competitive environment, culinary MSMEs owners need to have creativity and innovation to create quality products. Several researchers have found that leadership is an important factor in business development. Applying a creative and innovative leadership style is considered suitable for the culinary business because it can encourage creative and innovative behavior in the workplace, improve product quality, and meet customer expectations. This research aims to determine how creative and innovative leadership affects product quality (food, beverages, and services). This research also examines the direct impact of each aspect of creative and innovative leadership on product quality. The population of this research refers to the culinary MSMEs of Bandung City. The sampling technique used is the convenience sampling method. The sample used in this study was 102 respondents who were employees of various culinary MSMEs in Bandung City. Multiple linear regression analyses were used to test the proposed hypotheses. According to the findings of the data analysis, creative and innovative leadership has a positive impact on product quality. The dimension "inspiring creativity and innovation" has been shown to positively and significantly affect product quality. Based on the analysis results, creative and innovative leadership influences 41.4% of the quality of culinary products. This research also provides valuable recommendations for culinary business owners, especially in Bandung City, to support efforts to improve the quality of their products so they can compete in a competitive environment.